Determination of impurities in fixed vegetable oils - A. M. Kalinin; N. P. Antonova; S. S. Prokhvatilova; E. P. Shefer (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The review contains summary information about possible impurities, determination of which is described by draft monograph «fixed vegetable oils» and state standards of Russian Federation. The review briefly describes methods for determination of soaps, unsaponifiable components, residual solvents, volatile compounds, foreign fatty oils, aldehydes, moisture, proteins, paraffin, wax, tar and mineral oils, heavy metals, phosphorus-containing substances, cyanides and hydrogen cyanides.